2016
DOI: 10.1021/acs.energyfuels.6b00179
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptivity of a Hyper Cross-Linked Ionic Polymer Poly(vinyl imidazole)-1,4-bis(chloromethyl)benzene for Thiophenic Sulfurs in Model Oil

Abstract: A hyper cross-linked ionic polymer (HCIP) PVimBCmBn was synthesized through free radical polymerization of 1-vinylimidazole (Vim) and quaternized cross-linking with 1,4-bis­(chloromethyl) benzene (BCmBn). Its composition, structure, morphology, specific area, porous structure and thermal stability were characterized, and the desulfurization performance was investigated. The results show that the HCIP prepared with stoichiometric ratio of PVim and BCmBn are ultrafine powders with specific area of 99.6 m2·g–1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Methods to obtain hydrophilic membranes include the graft of polymers with antifouling characteristics. These materials are covalent bonded to the main chain of a polymeric matrix [ 7 , 8 , 9 , 10 ]. The graft of antifouling polymers enhances membrane permeability, performance and membrane lifetime, avoiding undesired interactions between both the membrane material and the feed solution [ 11 , 12 ]; meanwhile, the operation costs and environmental impacts in the membrane applications are also reduced by this process [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methods to obtain hydrophilic membranes include the graft of polymers with antifouling characteristics. These materials are covalent bonded to the main chain of a polymeric matrix [ 7 , 8 , 9 , 10 ]. The graft of antifouling polymers enhances membrane permeability, performance and membrane lifetime, avoiding undesired interactions between both the membrane material and the feed solution [ 11 , 12 ]; meanwhile, the operation costs and environmental impacts in the membrane applications are also reduced by this process [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calculated from the reciprocal of the slope, the saturated DBT adsorption capacity on P­[BPPIM] reached as high as 37.13 mgS·g –1 . According to our knowledge, it was the best one among the reported PILs, ,, and even larger than several typical porous materials, such as MCM-41, activated carbon, and MIL-100 (Table S3).…”
Section: Resultsmentioning
confidence: 88%
“…Copolymerization of ionic liquid monomers with the rigid aromatic vinyls ensured their high specific surface area, but the mass density of active IL groups in PPILs was low. Li et al 22 synthesized cross-linked PPILs through a two-step approach, in which the linear polymer was first obtained by the free radical polymerization of 1-vinylimidazolium, and followed by a quaternized cross-linking with 1,4-bis(chloromethyl) benzene. However, its specific surface area (99.6 m 2 •g −1 ) was not large enough for good desulfurization performance.…”
Section: Introductionmentioning
confidence: 99%
“…The highest uptake amount of 3-methylthiophene is observed in m -Cz-POF, which could reach 7.762 mmol/g (248.4 mg of S/g) at 298 K. This value is far beyond those of the porous absorbents previously reported (Figure ). ,,,, As for o -Cz-POF and p -Cz-POF, the maximum 3-methylthiophene absorption amounts are 6.266 and 7.599 mmol/g (200.5 and 243.2 mg of S/g), respectively, which indicated that the aromatic sulfide adsorption capacity was positively correlated with their surface area. The uptake of n -octane for o -Cz-POF, m -Cz-POF, and p -Cz-POF was 5.006, 6.238, and 5.903 mmol/g, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 92%